Access with(out) anonymity : anonymity in public libraries in modern times - Schepman, Tessie (Array, 2008)
Access to information is one aspect ; collecting and retaining data of people accessing information is another aspect of library services in modern times. Users can benefit from new technologies applied in library services, such as user profiles, based on loan history ; tailor made services through advanced marketing based on customer segmentation etc. Searching history on library internet computers, films with pictures of persons on security cameras are other data which may reveal a person’ s identity. Libraries as providers of services are legally and professionally obliged to guarantee anonymity to their users, meaning that users should remain unidentified, nameless, but in practice it more often means that their names are known to the providers of services, but should not be revealed to the greater public. A number of international IFLA/UNESCO documents on libraries, emphasize the libraries’ obligation to protect anonymity of their users, but do not provide a definition of anonymity in library nor a sufficient guideline for library practice. Therefore, the important and relevant question is: If libraries wish to deliver modern services – and they do so - to what extent should and could (public) libraries use or allow to use the above mentioned types of tools for collecting data? Is access to information only possible by giving up anonymity? Or can libraries give access to information safeguarding users’ anonymity? This article deals with these questions based on a research into relevant literature and legislation and a comparative survey of library practices and awareness of librarians in the Netherlands and Croatia.